2021
DOI: 10.1097/md.0000000000028059
|View full text |Cite
|
Sign up to set email alerts
|

GPR116 overexpression correlates with poor prognosis in gastric cancer

Abstract: The G protein-coupled receptor 116 (GPR116) is an adhesion subtype of the G protein-coupled receptor family and has been reported to be involved in tumorigenesis and cancer progression. Moreover, it has been shown to predict poor prognosis in breast and colorectal cancers. However, little is known about the role of GPR116 in gastric cancer (GC). In this study, we aimed to investigate the expression and clinical prognostic significance of GPR116 in GC.The mRNA expression levels of GPR116 in GC were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The occurrence and development of tumors are determined by many factors, including the relative activity of proto oncogenes and tumor suppressor genes, immune microenvironment, and inflammatory microenvironment 16 . The pro‐inflammatory nature of prognosis is related to the pathogenesis of many chronic inflammatory diseases 17,18 . Therefore, the inflammatory microenvironment formed by the release of a large number of inflammatory factors in the process of prognosis may promote the occurrence and development of tumors 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence and development of tumors are determined by many factors, including the relative activity of proto oncogenes and tumor suppressor genes, immune microenvironment, and inflammatory microenvironment 16 . The pro‐inflammatory nature of prognosis is related to the pathogenesis of many chronic inflammatory diseases 17,18 . Therefore, the inflammatory microenvironment formed by the release of a large number of inflammatory factors in the process of prognosis may promote the occurrence and development of tumors 16 .…”
Section: Discussionmentioning
confidence: 99%
“…16 The pro-inflammatory nature of prognosis is related to the pathogenesis of many chronic inflammatory diseases. 17,18 Therefore, the inflammatory microenvironment formed by the release of a large number of inflammatory factors in the process of prognosis may promote the occurrence and development of tumors. 16 Our results also showed that polysaccharide of L. casei SB27 suppressed IL-6, IL-17a, ptgs2 mRNA expressions in mice model of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…GPR116 has been reported to be involved in cancer progression and predicts poor prognosis in other types of cancer. The study [91] shows that GPR116 expression is upregulated in gastric cancer (GC) tissues and is positively correlated with tumor invasion and poor prognosis. GPR116 may be a novel prognostic marker and a potential therapeutic target for GC treatment.…”
Section: Pathway 1: Ctla4mentioning
confidence: 99%